ANALISIS POSTUR KERJA PADA BAGIAN GUDANG BARANG JADI MENGGUNAKAN METODERAPID ENTIRE BODY ASSESSMENT (REBA) - Zayyinul Hayati Zen; Beni Zamora (LPPM Universitas Muhammadiyah Riau, 2016)
PT. Indofood Sukses Makmur Tbk Div. Noodle Pekanbaru is a manufacturing company, producing instant noodles. These research focused on the finished goods warehouse. During the activities has been taken, most operator complained of pain in some parts of their body. The complaint will be identified by using Standard Nordic Questionnaire (SNQ). Then assestment of work posture by using Rappid Entire Body Assessment (REBA). Actual work conditions will be obtained, analyzed and evaluated. The results in the preparation of finished goods were the level of risk in moderate activity and needs improvement. On pull/pushment of finished goods to the warehouse location and to the dock, loading into the truck were a high level of risk activities and need to immediately repairs. Recommendations suggested are repositioning of operator’s working position, add giving sufficient space for laying pallet so that the operator more flexible. It also necessary to add tools for laying footing finished goods higher, adding safety devices backs operator.